The implementation of an ethnomathematics-based Flipbook–assisted problem-based learning model on students’ critical thinking skills based on cognitive style - Marlin Respita Rini; Detalia Noriza Munahefi; Angela Vivian Budianto (Universitas Sarjanawiyata Tamansiswa, 2026)
Critical thinking skills are essential in mathematics learning; however, students’ critical thinking skills at SMP Negeri 41 Semarang remain relatively low. This study aimed to determine the effectiveness of a Problem-Based Learning (PBL) model assisted by an ethnomathematics-based Flipbook of Semarang City on students’ critical thinking skills and to describe these skills based on cognitive style. The study employed a mixed-methods sequential explanatory design with a true experimental pretest–posttest control group design. The sample consisted of students from classes IX C and IX D in the 2025/2026 academic year, while six students were selected as qualitative subjects based on Field Independent (FI) and Field Dependent (FD) cognitive styles. The results show that the PBL model assisted by the Flipbook was effective, as indicated by individual and classical mastery . The experimental group achieved a higher N-Gain than the control group and showed a significant difference based on the Independent Samples t-test . Furthermore, students with a Field Independent cognitive style obtained a higher mean score than those with a Field Dependent cognitive style . Qualitative findings indicate that Field Independent students met critical thinking indicators well, while Field Dependent students met the indicators adequately. In conclusion, the PBL model assisted by an ethnomathematics-based Flipbook is effective in improving students’ critical thinking skills and reveals differences in performance based on cognitive style. This study contributes by providing an integrated instructional approach combining PBL, ethnomathematics, and digital Flipbook media while considering cognitive styles to enhance students’ critical thinking skills in mathematics learning.